2018
DOI: 10.1073/pnas.1721678115
|View full text |Cite
|
Sign up to set email alerts
|

PAX5-ELN oncoprotein promotes multistep B-cell acute lymphoblastic leukemia in mice

Abstract: PAX5 is a well-known haploinsufficient tumor suppressor gene in human B-cell precursor acute lymphoblastic leukemia (B-ALL) and is involved in various chromosomal translocations that fuse a part of PAX5 with other partners. However, the role of PAX5 fusion proteins in B-ALL initiation and transformation is ill-known. We previously reported a new recurrent t(7;9)(q11;p13) chromosomal translocation in human B-ALL that juxtaposed PAX5 to the coding sequence of elastin (ELN). To study the function of the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…One study hypothesized that loss of USP9X (seen in 4/17 CRLF2-rearranged cases), which encodes a deubiquitinase known to stabilize activated JAK2, may naturally buffer the toxic effect of JAK/STAT signaling hyperactivation in DS-ALL [67]. In addition, activating mutations in signaling effectors have been shown to functionally cooperate with loss of Ink4a/Arf and Pax5 alterations to drive B-cell leukemia development in vivo [75,76].…”
Section: Somatic Alterations Found In Ds-allmentioning
confidence: 99%
“…One study hypothesized that loss of USP9X (seen in 4/17 CRLF2-rearranged cases), which encodes a deubiquitinase known to stabilize activated JAK2, may naturally buffer the toxic effect of JAK/STAT signaling hyperactivation in DS-ALL [67]. In addition, activating mutations in signaling effectors have been shown to functionally cooperate with loss of Ink4a/Arf and Pax5 alterations to drive B-cell leukemia development in vivo [75,76].…”
Section: Somatic Alterations Found In Ds-allmentioning
confidence: 99%
“…PAX5 is a haplotype tumor suppressor gene in human B-All, which is involved in a variety of chromosome translocation ( Jamrog et al, 2018 ). In the investigation and analysis of Bastian et al (2019) , it was found that the army of patients with BCP-ALL subgroup carried PAX5 mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Such profiling has demonstrated the accuracy of mouse models of common translocations that occur in B-ALL/LBL, such as ETV6-RUNX1 , 59 MLL-AF4 , 27 and PAX5-ELN . 24…”
Section: Discussionmentioning
confidence: 99%